'More tight-less tight' Patterns in the Climatic Niche Evolution of Gymnocalycium (Cactaceae): Were Pleistocene Glaciations a Prelude? - Rahul Raveendran Nair; Alicia N Sérsic; Pablo H Demaio; Solana B Perotti; Diego E Gurvich (PLoS ONE)
Cacti have undergone some of the fastest diversification events in the plant kingdom despite their slow growth rates and extended generation times. This rapid evolution may be driven by intense ecological interactions. Here we tested, for the first time, the evolutionary dynamics of the ecological niches of Gymnocalycium species focusing on two key environmental factors: temperature and precipitation. To explore patterns of niche conservatism and/or evolution and identify major contributing factors, we reconstructed ancestral niches associated with these climatic dimensions using the binned ancestral range coding method. Our findings reveal that (1) the climatic-niches of narrow-ranged Gymnocalycium species are not highly conserved across the phylogeny (i.e., niches are evolving), (2) the evolutionary dynamics of thermal and precipitation niches across the Gymnocalycium phylogeny do not follow similar patterns, (3) a bioregion-specific pattern of niche evolution exists, and (4) the Early-Middle Pleistocene glaciations (i.e., GPG and three Post-GPG phases) potentially drove the patterns of lineage divergence in Gymnocalycium species, triggering the evolution of climatic niches. These results suggest that (i) Gymnocalycium species with fascicular roots may require special attention for conservation, (ii) in a warming climate, the species distributed in the South American transition zone, South Brazilian dominion, and Chacoan dominion may face serious risks, and (iii) the relatively 'more tight-less tight' pattern in conserving the precipitation and temperature niches could be a strategy for conserving the critical variable at the expense of the other. This study has not only provided valid insights into the evolutionary history of Gymnocalycium species but also highlights the importance of conservation efforts, essential to protect these species.